WARTAWAN DAN BUDAYA AMPLOP (BUDAYA AMPLOP PADA WARTAWAN PENDIDIKAN DALAM KAITANNYA DENGAN MEDIA RELATIONS) - Nurjanah, Adhianty; Widyasari, Wulan; Yulianti, Frizki Yulianti (Informasi, 2015)
Abstract Journalists play an important role as the fourth pillar of democracy. Doing so, journalists should be independent and separated from outside interference. This independence is not only applied to the relationship of journalistandthe government, but also applied to the relationship of journalists and news sources such as higher education institutions. In obtaining the proclamation of higher education institutions, journalists often intersect with public relations practitioners who also perform the task of media relations to gain publicity. This study aims to determine how to deal with the envelope cultureof journalists conducted by public relations practitioners of higher education institutions in Yogyakarta. The method used in this research is descriptive qualitative using interviews and focus group discussions on five journalists from famous print media in Yogyakarta, namely Kompas, Tribun, Harian Jogja, Kedaulatan Rakyat and Radar Jogja. The results of this study show that a good relationship between journalists and public relations practitioners play an important role in preventing the envelope culture and also, public relations practitioners need to have an understanding of newsworthy issues. In addition, journalismethics (KEJ) from the journalist associations can also be used as a strong reference in relation to the ban the envelope culture among journalists. Abstrak Wartawan memainkan peranan penting sebagai pilar ke-4 dalam demokrasi. Untuk itu wartawan harus bersikap independen dan terlepas dari intervensi pihak luar. Independensi ini tidak hanya berlaku pada hubungan wartawan dengan pemerintah saja, namun juga berlaku pada hubungan wartawan dengan sumber beritanya seperti institusi pendidikan tinggi. Dalam memperoleh pemberitaan dari institusi pendidikan tinggi, wartawan sering kali bersinggungan dengan praktisi public relations yang juga melakukan tugas media relations untuk memperoleh publikasi. Penelitian ini bertujuan untuk mengetahui bagaimana para wartawan menyikapi budaya amplop yang dilakukan oleh praktisi public relations institusi pendidikan tinggi di Yogyakarta. Metode penelitian yang digunakan dalam penelitian ini adalah deskriptif kualitatif dengan melakukan wawancara dan FGD pada lima orang wartawan dari media cetak di Yogyakarta, yaitu Kompas, Tribun, Harian Jogja, Kedaulatan Rakyat dan Radar Jogja. Hasil dari penelitian ini menunjukkan bahwa relasi yang baik antara wartawan dan praktisi public relations memainkan peranan penting dalam mencegah adanya budaya amplop dan perlu adanya strategi pengolahan isu yang bernilai berita. Selain itu, Kode Etik Jurnalistik (KEJ) yang dicetuskan asosiasi wartawan juga dapat dijadikan acuan yang kuat dalam kaitannya dengan larangan budaya amplop di kalangan wartawan. Keywords: Journalist, Envelope Culture, Journalism Ethics